Microencapsulated dietary supplementation coupled with sexual inversion improves the immune and antioxidant response of Nile tilapia larvae under stressful conditions - Casetta, Jaísa; Gasparino, Eliane; Ornaghi, Mariana Garcia; da Silva, Caroline Isabela; Toma, Anny Izumi; Oliveira, Gislaine Gonçalves; Ramos, Tatiane Rogelio; Lala, Bruno [UNESP]; Claudino-Silva, Stefania (My University, 2022)
In tilapia aquaculture, the cultivation of single-sex animals is extremely widespread, as it allows for the standardization of lots, in addition to improving the general performance of the animals. However, it is possible that hormonal inversion interacts with other factors, such as environmental and nutritional management, and modulates the immune response and antioxidant system of animals in a distinct manner. In order to test this hypothesis, an experiment was carried out using Nile tilapia larvae six days after hatching, divided into four experimental groups: NI (non-inverted animals), I (sexual inverted animals), NI + M (non-inverted supplemented with microencapsulated products) and I + M (sexual inverted and supplemented with microencapsulated products; half of which were subjected to transportation-related stress after 28 days of the experiment. At the end, the survival rate was evaluated; the gene expression of heat shock protein (HSP70), interleukin 1 beta (IL-1β) and cyclooxygenase-2 (COX 2) via RT-PCR; also evaluated were the activity of catalase (CAT) and superoxide dismutase (SOD) enzymes, as well as the total antioxidant capacity by 2,2-diphenyl-1-picryl-hydrazyl (DPPH). Animals from the I and I + M groups had the highest survival rate (p < 0.001) regardless of transportation stress. The highest expressions of HSP70 were found in the NI group (p < 0.001, with and without transportation). For the IL-1β gene, there was an increase in expression for animals belonging to groups NI and NI + M (no transportation); and NI (p < 0.0001, with transportation). Increased COX 2 expression was observed for all groups after transportation (p < 0.0001). The highest SOD activities were observed in groups I and I + M (without transportation, p = 0.0004), and I (with transportation, p < 0.0001). The transportation decreased the total antioxidant capacity of DPPH in all treatments (p < 0.001). Finally, when evaluating all of the results together, we came to a conclusion that sex inversion improves the immune response and antioxidant profile of animals under stressful conditions when associated with microencapsulated dietary supplementation.
Keywords: Antioxidant capacity; Immune response; Oreochromis niloticus; Sexual inversion; Supplementation; Tilapia